PERAN LITERASI KEUANGAN DALAM MEMODERASI PENGARUH DOOM SPENDING DAN FEAR OF MISSING OUT TERHADAP PERILAKU PENGELOLAAN KEUANGAN GENERASI Z DI KOTA KUPANG - Hernawati, Retno; Manek, Alfridus Mau (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2025)
This study aims to analyze the influence of Doom Spending and Fear of Missing Out (FOMO) on the financial management behavior of Generation Z in Kupang City, as well as to examine the role of financial literacy as a moderating variable in this relationship. The research employed a quantitative approach with purposive sampling, involving 398 respondents. Data were collected through a questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA). The findings reveal that Doom Spending and FOMO have a significant effect on the financial management behavior of Generation Z in Kupang City. Furthermore, financial literacy was found to act as a moderating variable, strengthening the relationship between Doom Spending, FOMO, and financial management behavior. The practical implication of this study highlights the importance of enhancing financial literacy through education, training, and digital media. Strengthening financial literacy will enable Generation Z to manage their finances more wisely and reduce excessive consumption behaviors triggered by Doom Spending and FOMO.